Age determination of Sterne (STE_L4) peat core from Canada - van Bellen, Simon (PANGAEA, 2021)
14C and 210Pb age determination of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Projec
Keywords: C-PEAT; Peatland